Improving Ipa Students’ Achievement In Green Growth Materials At The Fifth Grade Students Through Cooperative Learning Method Type Stad In Sdn 06 Perawang Barat 2013/ 2014 - Arianis Arianis (Jurnal Ilmiah Pendidikan Scholastic, 2017)
Teachers make various efforts to improve student learning outcomes. Therefore, it is needed a learning action that can enliven the students' motivation in achieving good values, individually or in groups. One way is to implement cooperative learning. In this learning students are required to work together in small groups to solve a problem and the group's primary goal is toward success. STAD type cooperative learning is based on an idea where students work together in a group and participate personally in the learning activities of their group members. Based on the background of the problems can be formulated as follows: "if the implementation of cooperative learning model STAD can improve learning outcomes of students in class V SDN 06 IPA in Perawang Barat in green plant matter?" The purpose of this research is to improve learning outcomes IPA fifth grade students of SDN 06 Perawang Barat on green plant material.The research method was classroom action research.This research was conducted at SDN 06 Perawang Barat.The research time is from February to May 2014. The subjects were students of class V SDN 06 Perawang Barat in academic year 2013/2014, amounting to 32 students consisting of 14 male - male and 18 female students.Instruments of the research areconsisting of syllabus, assessment system, lesson plan, and student work sheet. Based on the results, it can be concluded that the implementation of cooperative learning model STAD able to improve learning outcomes IPA class V SDN 06 in Perawang Barat. IPA students’ achievement